2011
DOI: 10.1021/tx200051s
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Genotoxicity of Size-Fractionated Iron Oxide (Magnetite) in A549 Human Lung Epithelial Cells: Role of ROS, JNK, and NF-κB

Abstract: Airborne particulate matter (PM) of varying size and composition is known to cause health problems in humans. The iron oxide Fe(3)O(4) (magnetite) may be a major anthropogenic component in ambient PM and is derived mainly from industrial sources. In the present study, we have investigated the effects of four different size fractions of magnetite on signaling pathways, free radical generation, cytotoxicity, and genotoxicity in human alveolar epithelial-like type-II cells (A549). The magnetite particles used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 67 publications
17
104
2
1
Order By: Relevance
“…In some studies, the mechanism seemed to be responsible for the genotoxicity was the ROS generation (158). In other studies, contradictory results were observed including peroxidase like activity of nanoparticles to reduce oxidative stress (159,160).…”
Section: Surface Chemistrymentioning
confidence: 99%
“…In some studies, the mechanism seemed to be responsible for the genotoxicity was the ROS generation (158). In other studies, contradictory results were observed including peroxidase like activity of nanoparticles to reduce oxidative stress (159,160).…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Several studies proposed oxidative stress as a key mechanism involved in the toxicity of various nanomaterials [31,[45][46][47] that results from the imbalance between excessive [12,31,40,48], which is based on the conversion of the non-fluorescent 2 0 ,7 0 -dichlorodihydrofluorescein diacetate to the highly fluorescent 2 0 ,7 0 -dichlorofluorescein; the substrate is oxidized preferentially by peroxides [39,49]. GO enhanced the formation of intracellular ROS in both A549 and RAW 264.7 cells at the highest concentration of 12.5 lg/cm 2 up to 3.5-times compared to control cells, already after 30 min (Fig.…”
Section: Generation Of Reactive Oxygen Species (Ros) By Graphene Oxidementioning
confidence: 99%
“…Several studies have examined the genotoxicity of nanosized magnetite particles; however, the data about this subject are incomplete and do not give a coherent picture. Konczol et al (2011) reported that treatment with magnetite nanoparticles induced ROS production, DNA damage as measured with the comet assay, and micronuclei (MN) formation in human alveolar epithelial-like type-II cells (A549 cells). On the other hand, they did not cause a significant increase in DNA damage or MN formation in Syrian hamster embryo cells (Guichard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Their chemical purities were similar as well (≥ 98% and > 99.5% in experiments by Konczol et al and Guichard et al, respectively). Furthermore, both groups reported that the nanoparticles were mainly present as aggregates or agglomerates in cell culture media, and they were incorporated into the cells (Konczol et al, 2011;Guichard et al, 2012). Thus, further toxicity studies are required to increase our understanding of the toxic potential of magnetite nanoparticles.…”
Section: Introductionmentioning
confidence: 99%